(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
Mainly in this article, the prospects for the development of the field of physical education and sports are to include the Republic of Uzbekistan in the ranks of developed countries, to form the foundations of a healthy lifestyle, to make the population value their health not only in words, but in practice, and consider it as a national value. it is emphasized that they need to be preserved.